Antiviral reflection preventing film, and optical product, and method for manufacturing antiviral reflection preventing film, and method for manufacturing optical product

By introducing metal ions to support zeolite antiviral layer in dielectric multilayer film and forming it under ultraviolet irradiation, the problem of insufficient antiviral performance of the existing antiviral transparent film is solved, and efficient antiviral and antireflective effects are achieved.

JP2025052732APending Publication Date: 2025-04-07TOKAI OPTICAL HOLDINGS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023161591
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

The existing antiviral transparent membrane has room for improvement in antiviral performance, especially under the unit content of zeolite supported by metal ions, which has insufficient antiviral performance.

Method used

Using a dielectric multilayer film containing metal ions supports zeolite, the antiviral performance is improved by forming a dielectric layer with low refractive index and high refractive index in the film, and an antiviral layer is included in it, which is formed under irradiation of high energy rays (such as ultraviolet light).

Benefits of technology

It significantly improves antiviral performance while maintaining antireflective performance, ensuring the optimization of light transmission mittance, and has high process feasibility and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052732000001_ABST
    Figure 2025052732000001_ABST
Patent Text Reader

Abstract

To provide an antiviral reflection preventing film having improved antiviral properties, an optical product, and a method for manufacturing an antiviral reflection preventing film, and a method for manufacturing an optical product.SOLUTION: An optical product 1 comprises a dielectric multilayer film 4 having reflection preventing properties. The dielectric multilayer film 4 includes one or more low refractive index dielectric layer 6, one or more high refractive index dielectric layer 8, and an antiviral layer 10. The antiviral layer 10 is a dielectric layer containing metal ion-carrying zeolite, arranged closer to an atmosphere than all low refractive index dielectric layers 6 and all high refractive index dielectric layers 8, and furthermore, the layer is irradiated with high-energy ray in the state of containing metal ion-carrying zeolite.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-reflective coating having anti-viral properties, an optical product, and a method for producing the same. [Background technology]

[0002] An antiviral transparent laminate is known, as described in JP 2022-109847 A (Patent Document 1). In this laminate, an antiviral layer containing 17 to 40% silver ion-supported zeolite is provided on an organic glass substrate. The antiviral layer does not require ultraviolet light to exert its antiviral properties because it contains zeolite supporting silver ions that have antiviral properties rather than photocatalytic properties. Furthermore, a superhydrophilic antifogging film or a water-repellent antifouling film is provided on the antiviral layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-109847 Summary of the Invention [Problem to be solved by the invention]

[0004] The laminate is endowed with antiviral properties. However, since the laminate contains zeolite carrying silver ions simply at a predetermined ratio, there is room for improvement in the antiviral performance per unit content of the zeolite, in other words, the antiviral performance according to the content of the zeolite. Therefore, a main object of the present disclosure is to provide an antiviral antireflective film and an optical product having improved antiviral properties, as well as a method for manufacturing an antiviral antireflective film and a method for manufacturing an optical product. [Means for solving the problem]

[0005] This specification discloses an antiviral antireflection film. The antiviral antireflection film may include a dielectric multilayer film having antireflection properties. The dielectric multilayer film may include one or more low refractive index dielectric layers, one or more high refractive index dielectric layers, and an antiviral layer. The antiviral layer may be a dielectric layer including metal ion-supported zeolite. The antiviral layer may be disposed closer to the atmosphere than all the low refractive index dielectric layers and all the high refractive index dielectric layers. The antiviral layer may be irradiated with high energy rays while including the metal ion-supported zeolite. This specification also discloses an optical product. The optical product may include the above-mentioned dielectric multilayer film and a substrate. The dielectric multilayer film may be formed directly or indirectly on the film-arrangement surface of the substrate. Furthermore, this specification discloses a method for producing an antiviral antireflective film. The method for producing the antiviral antireflective film may include a step of forming one or more low refractive index dielectric layers and one or more high refractive index dielectric layers alternately, and then forming a production intermediate antiviral layer that is a dielectric layer containing metal ion-supported zeolite, thereby forming a production intermediate film having antireflective properties. The method for producing the antiviral antireflective film may include a step of irradiating the production intermediate antiviral layer with high energy rays to make the production intermediate antiviral layer into an antiviral layer. Furthermore, the present specification discloses a method for manufacturing an optical product. The method for manufacturing an optical product may include a step of directly or indirectly forming the above-mentioned intermediate film on a film placement surface of a substrate. Effect of the Invention

[0006] A main effect of the present disclosure is to provide an antiviral antireflective film and an optical product having improved antiviral properties, as well as a method for manufacturing the antiviral antireflective film and a method for manufacturing the optical product. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view of an optical product according to the present disclosure. [Diagram 2]FIG. 2 is a schematic cross-sectional view of an antibacterial layer and an antifouling layer. [Diagram 3] 1 is a graph showing the spectral transmittance distribution in the visible range and adjacent ranges for each ultraviolet irradiation time for a single layer film. [Figure 4] 1 is a graph for a single layer film, with the horizontal axis representing the ultraviolet ray irradiation time (minutes) and the vertical axis representing the transmittance (%) at a wavelength of 400 nm. [Diagram 5] 1 is a flowchart showing a method for producing an antiviral antireflective coating. [Figure 6] 1 is a graph showing the spectral reflectance distribution in the visible range and adjacent ranges for Examples 1 and 2 and Comparative Example 1. [Figure 7] 1 is a graph showing the spectral reflectance distribution in the visible range and adjacent ranges for Examples 3 to 4 and Comparative Example 2. [Figure 8] 13 is a graph showing the spectral reflectance distribution in the visible range and adjacent ranges for Example 5 and Comparative Example 3. [Figure 9] 13 is a graph showing the spectral reflectance distribution in the visible range and adjacent ranges for Example 6 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, examples of embodiments according to the present disclosure will be described with reference to the accompanying drawings. The form is not limited to the following example.

[0009] FIG. 1 is a schematic cross-sectional view of an optical product 1 according to the present disclosure. The optical product 1 according to the present disclosure includes a substrate 2 , an intervening film 3 , and a dielectric multilayer film 4 .

[0010] The substrate 2 has light-transmitting properties. The substrate 2 is preferably made of plastic. The substrate 2 is a plastic lens substrate. The substrate 2 may be made of a material other than plastic, such as glass. The substrate 2 may be made of a plurality of materials, such as glass and plastic. The material for the substrate 2 is preferably a thermosetting resin, such as a polyurethane resin, a thiourethane resin, a urethane-urea resin, an episulfide resin, a polycarbonate resin, a polyester resin, an acrylic resin, a polyethersulfone resin, a poly-4-methylpentene-1 resin, a diethylene glycol bisallyl carbonate resin, or a combination thereof. The substrate 2 is preferably plate-shaped. The plate-shaped substrate 2 is also called a substrate. The substrate 2 is, for example, a spectacle lens substrate. The spectacle lens substrate may or may not have a power.

[0011] The dielectric multilayer film 4 is provided on one or more surfaces of the substrate 2. The dielectric multilayer film 4 is an anti-reflective film. The dielectric multilayer film 4 has anti-reflective properties. The surface of the substrate 2 on the inner side of the dielectric multilayer film 4 is the film placement surface F. When a plurality of dielectric multilayer films 4 are provided, the film configurations of the two or more dielectric multilayer films 4 are preferably identical to each other. When a plurality of dielectric multilayer films 4 are provided, the opposing surfaces of the plate-shaped substrate 2 are preferably provided as the respective film placement surfaces F. For ease of explanation, the following mainly describes the case where one dielectric multilayer film 4 is provided on one film placement surface F. The dielectric multilayer film 4 is provided via an intermediate film 3. The intermediate film 3 is a hard coat film. The dielectric multilayer film 4 may be formed directly on the film placement surface F, or may be formed via another type of intermediate film 3 instead of or together with the hard coat film. When a plurality of dielectric multilayer films 4 are provided, the types of intermediate films 3 added on the respective film placement surfaces F of the substrate 2 may be different from each other, or the presence or absence of the intermediate film 3 may be different from each other.

[0012] The hard coat film is preferably formed by uniformly applying a hard coat liquid onto the surface of the substrate 2 . Also, as the material of the hard coat film, an organosiloxane-based resin containing inorganic oxide fine particles can be preferably used. In this case, the hard coat liquid is preferably prepared by dispersing (mixing) a solute mainly composed of an organosiloxane-based resin and an inorganic oxide fine particle sol in a water or alcohol-based solvent. The organosiloxane-based resin is preferably obtained by hydrolyzing and condensing an alkoxysilane. Specific examples of the organosiloxane-based resin include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, methyltrimethoxysilane, ethyl silicate, or a combination thereof. These hydrolysis condensates of alkoxysilane are produced by hydrolyzing the alkoxysilane compound or a combination thereof with an acidic aqueous solution such as hydrochloric acid. On the other hand, specific examples of the material of the inorganic oxide fine particles include zinc oxide, silicon dioxide (silica fine particles), aluminum oxide, titanium oxide (titania fine particles), zirconium oxide (zirconia fine particles), tin oxide, beryllium oxide, antimony oxide, tungsten oxide, and cerium oxide sols, either alone or in combination of two or more of them. The diameter of the inorganic oxide fine particles is preferably 1 nm (nanometer) or more and 100 nm or less, more preferably 1 nm or more and 50 nm or less, from the viewpoint of ensuring the transparency of the hard coat film. In addition, the blending amount (concentration) of the inorganic oxide fine particles is preferably 40 wt% (mass percent) or more and 60 wt% or less of the total components of the hard coat film, from the viewpoint of ensuring at least one of the hardness and toughness of the hard coat film at an appropriate degree. In addition, at least one of acetylacetone metal salt and ethylenediaminetetraacetic acid metal salt may be added to the hard coat liquid as a curing catalyst. Furthermore, the hard coat liquid may contain surfactants, colorants, solvents, etc., depending on the needs of at least one of ensuring adhesion to the substrate 2 and facilitating formation. The physical thickness of the hard coat film is preferably 0.5 μm (micrometers) or more and 4.0 μm or less, and more preferably 1.0 μm or more and 3.0 μm or less. The lower limit of this film thickness range is determined because if the film thickness is thinner than this, it is difficult to obtain sufficient hardness. On the other hand, the upper limit is determined because if the film thickness is thicker than this, the possibility of problems related to physical properties such as cracks or brittleness occurring increases dramatically. Furthermore, from the viewpoint of improving the adhesion of the hard coat film, a primer film may be added as the intermediate film 3 between the hard coat film and the surface of the substrate 2. Examples of materials for the primer film include polyurethane resins, acrylic resins, methacrylic resins, organosilicon resins, and combinations thereof. The primer film is preferably formed by uniformly applying a primer liquid to the surface of the substrate 2. The primer liquid is preferably a liquid obtained by mixing the above-mentioned resin material and inorganic oxide fine particles in a water or alcohol-based solvent.

[0013] The dielectric multilayer film 4 includes one or more low refractive index dielectric layers 6, one or more high refractive index dielectric layers 8, an antiviral layer 10, and an antifouling layer 12. The antifouling layer 12 may be omitted. Alternatively, the antifouling layer 12 may be treated as an independent thin film rather than a component of the dielectric multilayer film 4.

[0014] From the viewpoint of obtaining good antireflection properties, the low refractive index dielectric layer 6 and the high refractive index dielectric layer 8 are preferably arranged in multiples and alternately arranged. The low refractive index dielectric layer 6 and the high refractive index dielectric layer 8 are preferably provided in a total of 5 or more layers (4 or more layers in total when the antiviral layer 10 plays the role of the low refractive index dielectric layer 6 or the high refractive index dielectric layer 8), and more preferably 7 or more layers in total (6 or more layers in total when the antiviral layer 10 plays the role of the low refractive index dielectric layer 6 or the high refractive index dielectric layer 8). 1, the first layer in the dielectric multilayer film 4, which is the layer closest to the substrate 2, is the low refractive index dielectric layer 6. Also, in FIG. 1, the adjacent layer in the dielectric multilayer film 4 adjacent to the antiviral layer 10 is the low refractive index dielectric layer 6. The total number of the low refractive index dielectric layers 6 and the high refractive index dielectric layers 8 in the dielectric multilayer film 4 in FIG. 1 is an odd number. The configuration of the dielectric multilayer film 4 is not limited to that of the dielectric multilayer film 4 in FIG. 1. For example, the first layer of the dielectric multilayer film 4 may be the high refractive index dielectric layer 8. In addition, the layer adjacent to the antiviral layer 10 may be the high refractive index dielectric layer 8.

[0015] The low refractive index dielectric layer 6 is preferably formed by vapor deposition of a low refractive index material. Examples of the low refractive index material include at least one of silicon oxide (particularly SiO2) and magnesium fluoride (particularly MgF2). The high refractive index dielectric layer 8 is preferably formed by vapor deposition of a high refractive index material. Examples of the high refractive index material include at least one of zirconium oxide (particularly ZrO2), titanium oxide (particularly TiO2), tantalum oxide (particularly Ta2O5), and niobium oxide (particularly Nb2O5). The deposition is preferably performed by vacuum deposition. Alternatively, deposition may be performed while assisted by at least one of oxygen ions and argon ions, or while performing plasma treatment. At least one of the low refractive index dielectric layer 6 and the high refractive index dielectric layer 8 may be formed by a method other than deposition, such as sputtering.

[0016] FIG. 2 is a schematic cross-sectional view of the antiviral layer 10 and the antifouling layer 12. The antiviral layer 10 is a dielectric layer containing metal particles 14. The metal particles 14 originate from metal ions supported by metal ion-supported zeolite. The metal particles 14 originate from metal ions, and are therefore metal ions. However, strictly speaking, to confirm whether or not all the metal particles 14 are present as metal ions in the antiviral layer 10 requires observation of a large number of samples using an electron microscope or the like, which is unrealistic because it requires a large amount of cost. In addition, there is a possibility that some of the metal particles 14 are not ions. Therefore, the metal particles 14 are described as metal particles 14 here, rather than as metal ions. The antiviral layer 10 is the layer in the dielectric multilayer film 4 that is furthest from the substrate 2, excluding the antifouling layer 12, i.e., the outermost layer. In other words, the antiviral layer 10 is the layer in the dielectric multilayer film 4 that is closest to the atmosphere, excluding the antifouling layer 12. When the antifouling layer 12 is not provided, the antiviral layer 10 is the layer in the dielectric multilayer film 4 that is furthest from the substrate 2 and the layer closest to the atmosphere.

[0017] The metal particles 14 in the antiviral layer 10 have antiviral properties. The metal ion-supported zeolite provides the metal particles 14 to the antiviral layer 10. The metal ion-supported zeolite is a material that imparts antiviral properties, i.e., an antiviral material. The metal particles 14 usually have antibacterial properties. The metal ion-supported zeolite is also a material that imparts antibacterial properties, i.e., an antibacterial material. The antiviral layer 10 does not necessarily have antibacterial properties. The metal ion-supported zeolite is formed by supporting metal particles 14 on zeolite (crystalline aluminosilicate) through an ion exchange reaction or the like. The general formula of zeolite is, for example, M n+ is an n-valent cation, M n+ 1 / n (AlO2) - (SiO2) x -yH2O. In zeolites, metal ions are supported in the pore structure created by Al. As the zeolite, at least one of natural zeolite (zeolite) and artificial zeolite may be used, and various types of zeolite such as A-type, Y-type, and P-type may be used. The metal particles 14 supported on the zeolite are, for example, at least one of silver ions, copper ions, and zinc ions. The metal ion-supported zeolite may support one type of metal particles 14 selected from these metal particles 14, or may support a combination of two or more types of metal particles 14. As the metal ion-supported zeolite, one type of metal ion-supported zeolite may be used alone, or two or more types of metal ion-supported zeolites may be used in combination. The metal particles 14 are preferably silver particles (silver ions) because they have excellent antiviral performance per unit mass and excellent durability against water. Therefore, the metal ion-supported zeolite is preferably silver ion-supported zeolite.

[0018] When a layer is formed of a metal ion-supported zeolite alone, which is an inorganic antibacterial material, the refractive index increases compared to the low refractive index dielectric layer 6. When a metal ion-supported zeolite is added to a deposition material related to a low refractive index dielectric, the refractive index of the formed layer increases, but the increase in the refractive index is mitigated compared to a layer of metal ion-supported zeolite alone. Therefore, the antiviral layer 10 preferably contains a low refractive index dielectric. The low refractive index dielectric is preferably SiO2 from the viewpoint of easier handling. In this case, in the antiviral layer 10, a structure derived from the metal ion-supported zeolite, which is a factor in increasing the refractive index, is added to the low refractive index dielectric. The refractive index of the antiviral layer 10 increases compared to the low refractive index dielectric layer 6 by the amount of the metal ion-supported zeolite contained therein, but the rate of increase is small. Therefore, the antiviral layer 10 can be optically treated in the same way as the low refractive index dielectric layer 6. Therefore, the desired optical characteristics are more easily ensured in the dielectric multilayer film 4.

[0019] The antiviral layer 10 is formed by irradiating a high-energy ray to an intermediate antiviral layer containing metal ion-supported zeolite. The antiviral layer 10 is formed by irradiating a high-energy ray to an intermediate antiviral layer containing metal ion-supported zeolite. The high-energy radiation is at least one of ultraviolet radiation, an electron beam, an ion beam, and an X-ray. Hereinafter, unless otherwise specified, ultraviolet radiation, which is a representative example, will be used to explain high-energy radiation. The explanation of ultraviolet radiation is also applicable when other high-energy radiations than ultraviolet radiation are used, and when ultraviolet radiation is used in combination with other high-energy radiations.

[0020] Irradiation with ultraviolet light mainly changes the properties of the intermediate antiviral layer during production, thereby obtaining the properties related to the antiviral layer 10. In order to grasp the change in the characteristics, especially the change in the transmittance characteristics, the spectral transmittance distribution of the intermediate antiviral layer formed on the substrate or the monolayer film corresponding to the antiviral layer 10 was measured at predetermined time intervals of ultraviolet irradiation. The substrate was made of glass in this example to avoid the change in the spectral transmittance distribution of the substrate itself due to ultraviolet irradiation. The monolayer film contains 50 parts by mass of silver ion-supported zeolite and 50 parts by mass of SiO2. That is, the wt% of the silver ion-supported zeolite in the monolayer film is 50 wt%. The physical film thickness of the monolayer film is 50 nm. The ultraviolet irradiation at predetermined time intervals was performed for 0 minutes (i.e., before ultraviolet irradiation, corresponding to the intermediate antiviral layer), 5 minutes, 10 minutes, 15 minutes, and 20 minutes. The ultraviolet irradiation was performed in the atmosphere using an ultraviolet lamp (H bulb manufactured by Heraeus Noble Light Japan Co., Ltd.). The light amount of this ultraviolet lamp was 3.84 J / cm per minute in the wavelength range of 320 nm to 390 nm. 2 (Joules per square centimeter). The spectral transmittance distribution relates to the visible range and adjacent ranges. The visible range here is from 400 nm to 780 nm inclusive.

[0021] As shown in Fig. 3, the spectral transmittance distribution of the monolayer film after UV irradiation shifts to the lower transmittance side as the UV irradiation time increases compared to the spectral transmittance distribution of the monolayer film before UV irradiation. The decrease in transmittance is remarkable in the wavelength range of 360 nm to 600 nm. 4 is a graph of a single layer film, with the horizontal axis representing the UV irradiation time (minutes) and the vertical axis representing the transmittance (%) at a wavelength of 400 nm. The transmittance of the single layer film decreases as the UV irradiation time increases. The degree of decrease in the transmittance decreases as the UV irradiation time increases. The degree of decrease in the transmittance is particularly severe, with a decrease of more than one point up to a UV irradiation time of 10 minutes. The decrease in transmittance of the monolayer film is due to light absorption, not light reflection. That is, the extinction coefficient of the monolayer film after ultraviolet irradiation, which corresponds to the antiviral layer 10, is greater than that of the monolayer film before ultraviolet irradiation, which corresponds to the intermediate antiviral layer during production. The longer the ultraviolet irradiation time, the greater the extinction coefficient of the monolayer film before and after ultraviolet irradiation, the greater the amount of light absorption, and the greater the decrease in transmittance. The refractive index of the monolayer film is almost the same between the intermediate antiviral layer before ultraviolet irradiation and the antiviral layer 10 after ultraviolet irradiation. Such a decrease in transmittance due to an increase in the UV irradiation time indicates that the UV rays change the microstructure of the intermediate antiviral layer to the microstructure of the antiviral layer 10. In other words, the decrease in transmittance indicates that the microstructure of the intermediate antiviral layer before UV irradiation and the microstructure of the antiviral layer 10 after UV irradiation are different from each other.

[0022] The antiviral property of the antiviral layer 10 after ultraviolet irradiation is higher than that of the intermediate antiviral layer before ultraviolet irradiation. The antiviral performance of the film containing metal ion-supported zeolite is increased by ultraviolet irradiation. The reason for this increase is presumed to be as follows. The ultraviolet light irradiation locally reaches the metal particles 14 and their adjacent portions without changing the basic structure of the dielectric multilayer film 4. The ultraviolet light mainly acts on the intermediate antiviral layer in the intermediate film, causing a structural change from the microstructure of the intermediate antiviral layer to the microstructure of the antiviral layer 10. Irradiation with ultraviolet rays changes the relationship between the metal particles 14 and oxygen atoms in the antiviral layer 10 compared to the relationship between the metal particles 14 and oxygen atoms in the intermediate antiviral layer. For example, when the metal particles 14 are silver particles, in a part or all of a microscopic structure of the intermediate antiviral layer before ultraviolet irradiation, which resembles Ag2O in which silver particles are surrounded by oxygen atoms, irradiation with ultraviolet rays causes the silver particles to be released from the surrounding oxygen atoms and precipitate in the antiviral layer 10. Note that a similar phenomenon also occurs in the metal particles 14 when irradiated with high-energy rays other than ultraviolet rays. It is generally known that free electrons in silver particles with a diameter of 10 nm to 100 nm oscillate when irradiated with light within a specific wavelength range depending on the particle diameter distribution. This oscillation phenomenon of free electrons is called surface plasmon resonance. Surface plasmon resonance is caused by coupling with light within a specific wavelength range depending on the particle diameter distribution. It is considered that surface plasmon resonance or a similar phenomenon occurs when light within a specific wavelength range depending on the particle diameter distribution is irradiated to an intermediate antiviral layer containing metal ion-supported zeolite containing metal particles 14. The extinction coefficient of the antiviral layer 10 increases due to surface plasmon resonance or a similar phenomenon, and light absorption occurs in the antiviral layer 10, resulting in a decrease in the transmittance of the antiviral layer 10. The wavelength range in which the decrease in transmittance occurs corresponds to the wavelength range in which the metal particles 14 and surface plasmon resonance or a similar phenomenon occur, and depends particularly on the diameter of the metal particles 14. 3, the transmittance of the antiviral layer 10 after ultraviolet irradiation is reduced in the wavelength range of 360 nm or more and 600 nm or less, and is particularly reduced significantly at or around a wavelength of 400 nm. It is considered that the metal particles 14 precipitated in the antiviral layer 10 by irradiation with high-energy rays have a diameter of about 10 nm or more and 100 nm or less due to surface plasmon resonance or a similar phenomenon.

[0023] The actual microscopic physical structures of the manufactured intermediate film containing the metal particles 14 and the dielectric multilayer film 4 before and after ultraviolet irradiation are not easily understood. The metal particles 14 have a lower density than when they are spread all over the surface of the manufactured intermediate film and the surface of the dielectric multilayer film 4, making it difficult to analyze the valence distribution of the metal ions by X-ray photoelectron spectroscopy (XPS). In addition, it is currently difficult to accurately observe the dielectric multilayer film 4 using an electron microscope such as a field emission scanning electron microscope (FE-SEM) because the electron beam irradiation for observation causes changes in the state of the dielectric multilayer film 4, such as the metal particles 14 being pulled by the electron beam or the metal particles 14 being precipitated by the energy of the electron beam. Thus, the actual microstructure of the manufactured intermediate film and the dielectric multilayer film 4 is difficult even for those skilled in the art, and is also impractical in terms of cost. Therefore, for example, the virus layer 10 can be expressed as a layer formed from a material containing metal ion-supported zeolite and irradiated with ultraviolet light. Alternatively, the antiviral layer 10 can be expressed as a layer containing metal ion-supported zeolite and irradiated with ultraviolet light. Alternatively, the antiviral layer 10 can be expressed as a layer containing metal ion-supported zeolite, SiO2, and Al2O3 and irradiated with ultraviolet light.

[0024] From the viewpoint of obtaining sufficient antiviral performance, the lower limit of the ultraviolet irradiation time is preferably 8 minutes, 5 minutes, 3 minutes, 2 minutes, and 1 minute in this order. From the viewpoint of good efficiency of film formation, the upper limit of the ultraviolet irradiation time is preferably 5 minutes, 10 minutes, 15 minutes, and 20 minutes in this order. From the viewpoint of efficiently obtaining a change in the antiviral layer 10 for improving the antiviral properties, which is inferred from the change in the transmittance characteristics of the monolayer film, the ultraviolet irradiation time is particularly preferably 5 minutes or more and 10 minutes or less. From the viewpoint of obtaining sufficient antiviral performance in the antiviral layer 10 obtained by irradiation with ultraviolet rays, the lower limit of a preferred range of the mass ratio, which is the ratio of the mass of the metal ion-supported zeolite to the total mass in the antiviral layer 10, is, for example, 30 wt%, 35 wt%, or 38 wt%. From the viewpoint of reducing the amount of material used, easiness in designing the dielectric multilayer film 4 including the antiviral layer 10, and easiness in obtaining sufficient optical performance, the upper limit of the preferred range of the mass ratio is, for example, 60 wt%, 50 wt%, or 40 wt%. The mass ratio, which is the ratio of the mass of the metal ion-supported zeolite to the total mass in the antiviral layer 10, is expressed in units of wt% by the following formula (1). The total mass here is the mass of the antiviral layer 10. When the antiviral layer 10 is vapor-deposited, the mass ratio in the antiviral layer 10 corresponds to the mass ratio in the vapor-deposition material. Mass ratio = mass of metal ion-supported zeolite / total mass × 100 (1)

[0025] A preferable physical film thickness of the antiviral layer 10 is determined by balancing the improvement of antiviral performance with the suppression of the occurrence of abnormalities in appearance, the suppression of an increase in the refractive index, and the suppression of a decrease in antireflection properties. The larger the physical film thickness of the antiviral layer 10, the more the metal particles 14 are increased, and the better the antiviral performance. In general, to obtain antiviral properties, an amount of metal particles 14 that exceeds the amount of metal particles 14 required for antibacterial properties is required. Therefore, the antiviral layer 10 requires a larger amount of metal ion-supported zeolite than when forming an antibacterial layer. On the other hand, if the physical film thickness of the antiviral layer 10 is too large, the possibility of occurrence of abnormal appearance increases, and an increase in the refractive index becomes difficult to ignore. In addition, it becomes difficult to suppress a decrease in antireflection properties, for example, by disposing the antiviral layer 10 as the outermost layer excluding the antifouling layer 12 in a state where it does not deviate from the layer structure of the antireflection film. Therefore, the lower limit of the preferable range of the physical thickness of the antiviral layer 10 is, for example, 30 nm, 40 nm, or 50 nm, and the upper limit of the preferable range of the physical thickness of the antiviral layer 10 is, for example, 100 nm, 90 nm, or 80 nm.

[0026] The antiviral function of the antiviral layer 10 is believed to be exerted as follows. That is, as shown in Fig. 2, the antiviral function of the antiviral layer 10 is mainly exerted by surface metal particles 14A, which are metal particles 14 and are arranged on the surface layer of the antiviral layer 10 and may come into contact with viruses, etc. The metal particles 14, including the surface metal particles 14A, inactivate viruses that they come into contact with. For example, enveloped viruses have spikes that bind to receptors in the body, and the spikes have SH groups, which easily react with the metal particles 14, and the spikes are covered with the metal particles 14. Therefore, the receptor-binding function of the spikes is inhibited by the metal particles 14, and the viruses are inactivated. On the other hand, it is known that in an antibacterial film with a physical thickness of 100 nm that is deposited on one side of a substrate using a sintered body obtained by sintering silver ion-supported zeolite and SiO2 together, and that has not been irradiated with high-energy rays, silver atoms are present uniformly in the depth direction of the antibacterial film, maintaining a certain atomic concentration range. That is, a graph showing the relationship between etching depth (horizontal axis) and atomic concentration (vertical axis) measured by X-ray photoelectron spectroscopy (XPS) using ion etching, which was presented in Program 2.3 "Evaluation of various physical properties and antibacterial activity of thin films made from antibacterial deposition materials" of the 36th Optical Thin Film Research Meeting, held online on November 10, 2020, shows that the silver atomic concentration ranges from 10 to 100 nm from an etching depth of 0 nm (surface) to 100 nm (interface with the substrate). -2.1 ~10 -1.5 It is described that silver atoms are present within the range of [%]. Therefore, in an antibacterial film made of a sintered body obtained by combining silver ion-supported zeolite and SiO2 and sintering them, silver atoms are present uniformly in the depth direction. Therefore, similar to such an antibacterial film, it can be said that the metal particles 14 in the antiviral layer 10 are uniformly present in the depth direction before ultraviolet irradiation. If the amount of metal ion-supported zeolite increases and the proportion of the metal ion-supported zeolite in the antiviral layer 10 increases, the surface metal particles 14A also increase accordingly. As described above, the metal particles 14 are precipitated by irradiation with high energy rays, and if the amount of metal ion-supported zeolite increases and the proportion of the metal ion-supported zeolite in the antiviral layer 10 increases, the amount of the precipitated metal particles 14 also increases, and the surface metal particles 14A also increase accordingly. Therefore, the antiviral function of the antiviral layer 10 is better exhibited as the proportion of the metal ion-supported zeolite in the antiviral layer 10 increases. The antiviral function of the antiviral layer 10 is better exhibited by irradiation with ultraviolet rays.

[0027] The antifouling layer 12 is disposed on top of the antiviral layer 10, i.e., on the atmospheric side of the antiviral layer 10. The antifouling layer 12 imparts an antifouling function to the optical product 1. The antifouling function includes at least one of a water repellent function and an oil repellent function. The antifouling layer 12 is formed by a known method such as vapor deposition or ion sputtering.

[0028] The antifouling layer 12 is formed by, for example, polycondensation of an organosilicon compound. Polycondensation enables the coating to be thickened and dense, and increases the adhesion to adjacent layers in the dielectric multilayer film 4 and the surface hardness. Thus, the antifouling layer 12 exhibits oil repellency in addition to water repellency. Also, the antifouling layer 12 is easily formed into a coating that is excellent in the wipeability of dirt. The organosilicon compound before polycondensation is preferably -SiR y X 3-y (R is a monovalent organic group, X is a hydrolyzable group, and y is an integer from 0 to 2). Here, X is, for example, an alkoxy group such as -OCH3 or -OCH2CH3, an acyloxy group such as -OCOCH3, -ON=CR a R b Ketoxime groups (R a ,R b each represents a monovalent organic group), halogen groups such as -Cl and -Br, -NR c R d Amino groups such as (R c ,R d Each of the groups represents a monovalent organic group. As such an organosilicon compound, a fluorine-containing organosilicon compound is suitable. Fluorine-containing organosilicon compounds are excellent in water and oil repellency, electrical insulation, mold releasability, solvent resistance, lubricity, heat resistance, and defoaming properties. In particular, organosilicon compounds having a relatively large molecular weight of about 1000 to 50000 and having a perfluoroalkyl group or perfluoropolyether group in the molecule are excellent in antifouling properties.

[0029] Since the antifouling layer 12 has an antifouling function, it has a molecular structure with larger gaps than other layers. Therefore, the antiviral effect of the antiviral layer 10 directly below is not blocked by the antifouling layer 12.

[0030] The dielectric multilayer film 4 can provide the optical product 1 with optical functions and optical characteristics. For example, the optical function is at least one of an anti-reflection function and a blue light cut function. Also, for example, the optical characteristic is at least one of an anti-reflection characteristic and a blue light cut characteristic. Furthermore, the anti-soiling layer 12 of the dielectric multilayer film 4 imparts an anti-soiling function and anti-soiling properties to the optical product 1 .

[0031] As shown in FIG. 5, the manufacturing method of the dielectric multilayer film 4 includes forming a manufactured intermediate film by physical vapor deposition (step S1), irradiating the manufactured intermediate film with high-energy rays (step S2), determining whether or not an anti-fouling layer 12 is present (step S3), and forming the anti-fouling layer 12 (step S4).

[0032] In step S1, the intermediate film of the dielectric multilayer film 4 is formed by physical vapor deposition using three kinds of vapor deposition materials. The vapor deposition materials are materials containing a low refractive index dielectric material, a high refractive index dielectric material, and metal ion-supported zeolite. The intermediate film of the dielectric multilayer film 4 is formed corresponding to the film placement surface F of the substrate 2 on which the intervening film 3 is formed. The material containing metal ion-supported zeolite is preferably a sintered body obtained by sintering a combination of metal ion-supported zeolite and a low refractive index dielectric. The intermediate film of the dielectric multilayer film 4 is a vapor deposition film. The low refractive index dielectric layer 6 in the fabrication interlayer is preferably formed by vacuum deposition of a low refractive index dielectric material. The high refractive index dielectric layer 8 in the fabrication interlayer is preferably formed by vacuum deposition of a high refractive index dielectric material. The intermediate antiviral layer in the intermediate film is preferably formed by vacuum deposition of the above-mentioned sintered body. Preferably, the sintered body is prepared by sintering together silver ion-supported zeolite and SiO2. The molecular structure of the intermediate antiviral layer in the intermediate film is similar to the molecular structure of SiO2 and Al2O3 when vapor-deposited. This is because at least a part of zeolite, which is an aluminosilicate, behaves like SiO2 and Al2O3 during vapor deposition. Identifying the molecular structure of the intermediate film in the intermediate film in the antiviral layer 10 may differ for each vapor deposition, and many samples must be thoroughly observed using an electron microscope or the like, which is difficult even for those skilled in the art and is also impractical in terms of cost. Therefore, for example, the intermediate antiviral layer can be expressed as a layer formed from a material containing metal ion-supported zeolite. Alternatively, the intermediate antiviral layer can be expressed as a layer containing metal ion-supported zeolite. Alternatively, the intermediate antiviral layer can be expressed as a layer containing metal ion-supported zeolite, SiO2, and Al2O3.

[0033] In step S2, a high-energy ray is irradiated onto the intermediate film of the dielectric multilayer film 4. The intermediate film becomes the dielectric multilayer film 4 by the irradiation of the high-energy ray. As described above, ultraviolet rays are a typical example of high-energy rays, and the high-energy rays will be described here mainly using ultraviolet rays as a representative example.

[0034] The ultraviolet irradiation is preferably performed by applying light from an ultraviolet lamp to the intermediate film produced. The ultraviolet lamp may be disposed within the deposition apparatus, such as within a vacuum chamber, or may be disposed outside the deposition apparatus. From the viewpoint of improving the action of ultraviolet light on the metal ion-supported zeolite, ultraviolet light is preferably irradiated directly onto the intermediate antiviral layer, which is the outermost layer of the intermediate film. Alternatively, ultraviolet light may be irradiated onto the intermediate antiviral layer after the intermediate film is further provided with an antifouling layer 12.

[0035] Then, if the design of the dielectric multilayer film 4 includes an antifouling layer 12 (Yes in step S3), the antifouling layer 12 is formed on the antiviral layer 10 after ultraviolet irradiation (step S4), and the manufacture of the dielectric multilayer film 4, i.e., the antiviral antireflective film, is completed. Note that, if ultraviolet irradiation is performed outside the deposition apparatus, the manufactured intermediate film is returned to the deposition apparatus again, and the antifouling layer 12 is deposited. Also, the antifouling layer 12 may be formed in an apparatus different from the deposition apparatus for the manufactured intermediate film. On the other hand, if the antifouling layer 12 is not included in the design of the dielectric multilayer film 4 (No in step S3), the manufacture of the dielectric multilayer film 4 ends immediately. EXAMPLES

[0036] Examples belonging to the present disclosure and comparative examples not belonging to the present disclosure are shown below. The following examples are not intended to limit the scope of the disclosure. Depending on how the present disclosure is interpreted, some of the following examples may essentially be comparative examples, or some of the following comparative examples may essentially be examples.

[0037] Examples 1 to 6 belonging to Optical Product 1 and Comparative Examples 1 to 4 not belonging to Optical Product 1 were produced. The material of each layer in Examples 1 to 4 and Comparative Examples 1 and 2, the refractive index for light with a wavelength of 500 nm, and the physical film thickness are shown in Table 1 below. The material of each layer in Examples 5 to 6 and Comparative Examples 3 and 4, the refractive index for light with a wavelength of 500 nm, and the physical film thickness are shown in Table 2 below.

[0038] [Table 1]

[0039] [Table 2]

[0040] The substrate 2 in each of Examples 1 to 6 and Comparative Examples 1 to 4 is the same as one another. The refractive index of the substrate 2 is 1.60. The material of the substrate 2 is a thiourethane resin. The substrate 2 is a spectacle lens substrate, and is a spherical lens with a diopter of S-2.00. The intermediate film 3 in each of Examples 1 to 6 and Comparative Examples 1 to 4 is the same as one another. The intermediate film 3 is a hard coat film. The refractive index of the intermediate film 3 is 1.60. The material of the intermediate film 3 is a thermosetting silicone resin. The physical thickness of the intermediate film 3 is 2.0 μm. In each of Examples 1 to 6 and Comparative Examples 1 to 4, the intermediate films 3 having the same configuration are provided on the front and back of the substrate 2. More specifically, the intervening film 3 is formed as follows. That is, 206g of methanol, 300g of methanol-dispersed titania sol (manufactured by JGC Catalysts and Chemicals, solid content 30%), 60g of γ-glycidoxypropyltrimethoxysilane, 30g of γ-glycidoxypropylmethyldiethoxysilane, and 60g of tetraethoxysilane are dropped into a reaction vessel, and 0.01N aqueous hydrochloric acid solution is dropped into the mixture and stirred to perform hydrolysis. Next, 0.5g of flow regulator and 1.0g of catalyst are added, and the mixture is stirred at room temperature for 3 hours to form a hard coat liquid. This hard coat liquid is applied to both sides of the substrate 2, and heat cured at 120°C for 1.5 hours to form a hard coat film with a thickness of 2.0 μm.

[0041] Each of the dielectric multilayer films 4 in Examples 1 to 6 and Comparative Examples 1 to 4 is an anti-reflection film. In each of Examples 1 to 6 and Comparative Examples 1 to 4, the dielectric multilayer films 4 having the same configuration are provided on the intervening films 3 having the same configuration on the front and back sides of the substrate 2. Each of the low refractive index dielectric layers 6 in Examples 1 to 6 and Comparative Examples 1 to 4 is a SiO2 layer that is a layer made of SiO2. The refractive index of each of the SiO2 layers is 1.470. Each of the SiO2 layers is deposited by vapor deposition using SiO2 as a material. Each of the high refractive index dielectric layers 8 in Examples 1 to 6 and Comparative Examples 1 to 4 is a ZrO2 layer made of ZrO2. The refractive index of the ZrO2 layer is 2.106. Each of the ZrO2 layers is deposited by vapor deposition using ZrO2 as the material. The first to fourth layers of Examples 1 to 6 and Comparative Examples 1 to 4 have the same configuration. The first layer is a 32 nm thick SiO2 layer. The second layer is a 37 nm thick ZrO2 layer. The third layer is a 24 nm thick SiO2 layer. The fourth layer is a 51 nm thick ZrO2 layer.

[0042] Each of the intermediate antiviral layers in Examples 1 to 6 was formed by vapor deposition using a sintered body obtained by combining and sintering silver ion-supported zeolite and SiO2 as a vapor deposition material. The mass ratio of each component in the sintered body is silver ion-supported zeolite:SiO2=5:5 in Examples 1 to 4, and silver ion-supported zeolite:SiO2=4:6 in Examples 5 to 6. "SiO2+AgZL 50wt%" in Table 1 indicates that AgZL, i.e., silver ion-supported zeolite, is combined with SiO2 at a ratio of 50wt%. "SiO2+AgZL 40wt%" in Table 2 indicates that silver ion-supported zeolite is combined with SiO2 at a ratio of 40wt%.

[0043] The left side of Table 3 below shows the proportion (wt%) of silver ion-supported zeolite, physical film thickness (nm), presence or absence of antifouling layer 12, and UV irradiation time (minutes) for antiviral layer 10 (the sixth layer in Examples 1 to 5, and the fifth layer in Example 6) or the layer corresponding to an intermediate antiviral layer during production (the sixth layer in Comparative Examples 1 to 3, and the fifth layer in Comparative Example 4).

[0044] [Table 3]

[0045] The ultraviolet irradiation was performed in the same manner as in the case of the single layer film described above. The ultraviolet irradiation time in Examples 1, 3, and 5 was 5 minutes. The ultraviolet irradiation time in Examples 2, 4, and 6 was 10 minutes. The refractive index of each of the antiviral layers 10 obtained by irradiating the intermediate antiviral layer with ultraviolet light was 1.510 in Examples 1 to 4, and 1.483 in Examples 5 and 6. The antiviral layer 10 in Examples 1 to 4 is the sixth layer, and its physical thickness is 50 nm. In Examples 1 to 4, the fifth layer, the SiO2 layer adjacent to the antiviral layer 10 on the substrate side, has a physical thickness of 50 nm. The antiviral layer 10 in Example 5 is the sixth layer, and has a physical thickness of 30 nm. In Examples 1 to 4, the fifth layer, which is an SiO2 layer adjacent to the antiviral layer 10 on the substrate side, has a physical thickness of 70 nm. The antiviral layer 10 in Example 6 is the fifth layer, and its physical thickness is 100 nm. The physical thickness of the fourth ZrO2 layer adjacent to the antiviral layer 10 on the substrate side is 51 nm as described above. In Examples 1 to 5, each antiviral layer 10 and the adjacent low refractive index dielectric layer 6, i.e., the SiO2 layer, have optical identity with the adjacent SiO2 layer from the viewpoint of refractive index similarity. In Examples 1 to 5, from the viewpoint of maintaining the same antireflection properties, the sum of the physical film thickness of each antiviral layer 10 and the physical film thickness of the SiO2 layer adjacent to that antiviral layer 10 is 100 nm, which is the same as each other. In Example 6, the total physical film thickness of the antiviral layer 10, which is the fifth layer and contains SiO2, is 100 nm.

[0046] The sixth layer in Comparative Examples 1 to 3 is similar to the sixth layer in Examples 1 to 5, except that it is not irradiated with ultraviolet light. The fifth layer in Comparative Example 4 is similar to the fifth layer in Example 6, except that it is not irradiated with ultraviolet light. The sixth layer in Comparative Examples 1 to 3 and the fifth layer in Comparative Example 4 correspond to intermediate antiviral layers during production.

[0047] Furthermore, only in Examples 3 to 4 and Comparative Example 2, the antifouling layers 12 are contained in the dielectric multilayer films 4 on the front and back sides. Each of the antifouling layers 12 in Examples 3 to 4 and Comparative Example 2 was formed by vapor deposition of OF-SR manufactured by Canon Optron Inc. The physical thickness of each of the antifouling layers 12 was 5 nm. In Examples 3 and 4, after the antiviral layer 10 has been vacuum-deposited, the substrate is temporarily removed from the chamber and irradiated with ultraviolet light, and then returned to the chamber where the antifouling layer 12 is formed.

[0048] Then, tests were conducted on the performance of each of Examples 1 to 6 and Comparative Examples 1 to 4. The tests included measurement of the spectral reflectance distribution and an antiviral test.

[0049] The spectral reflectance distributions of Examples 1 to 6 and Comparative Examples 1 to 4 were measured in the visible range and adjacent ranges. Fig. 6 is a graph showing the spectral reflectance distribution in the visible range and its adjacent ranges for Examples 1 and 2 and Comparative Example 1. Fig. 7 is a graph showing the spectral reflectance distribution in the visible range and its adjacent ranges for Examples 3 and 4 and Comparative Example 2. Fig. 8 is a graph showing the spectral reflectance distribution in the visible range and its adjacent ranges for Example 5 and Comparative Example 3. Fig. 9 is a graph showing the spectral reflectance distribution in the visible range and its adjacent range for Example 6 and Comparative Example 4. According to these figures, Examples 1 to 6 and Comparative Examples 1 to 4 all have a reflectance of 2.5% or less over the entire visible range, and thus have anti-reflection properties over the visible range. In particular, Examples 1 to 2, 5 to 6 and Comparative Examples 1, 3 to 4, which do not have the antifouling layer 12, have a reflectance of 2.1% or less over the entire visible range, while Examples 5 to 6 and Comparative Examples 3 to 4 have a reflectance of 2.0% or less over the entire visible range.

[0050] The refractive indexes at a wavelength of 500 nm of the sixth layer in Comparative Examples 1 to 3 and the fifth layer in Comparative Example 4 are similar to the refractive indexes of the corresponding antiviral layers 10 of the Examples. That is, even when the sixth layer in Comparative Examples 1 to 3 and the fifth layer in Comparative Example 4 are irradiated with ultraviolet light to produce the antiviral layers 10 of the corresponding Examples, the refractive indexes at a wavelength of 500 nm do not change. On the other hand, the extinction coefficients in the wavelength range of 360 nm or more and 600 nm or less of the sixth layer of Comparative Examples 1 to 3 and the fifth layer of Comparative Example 4 are smaller than the corresponding extinction coefficients of the antiviral layer 10 of the corresponding Example. That is, when the sixth layer of Comparative Examples 1 to 3 and the fifth layer of Comparative Example 4 are irradiated with ultraviolet light to form the antiviral layer 10 of the corresponding Example, the extinction coefficients increase. 6 to 9, the reflectance in the wavelength region of 360 nm to 600 nm in each Example is not significantly different from the reflectance in the corresponding Comparative Example before UV irradiation, and the reflectance of the former is not significantly higher than that of the latter. In other words, even when each Comparative Example is irradiated with UV light to produce a corresponding Example, the reflectance does not increase to such an extent that the anti-reflection properties are impaired, and the anti-reflection properties are maintained in each Example regardless of UV irradiation.

[0051] Furthermore, for Examples 1 to 6 and Comparative Examples 1 to 4, antiviral tests were conducted in accordance with ISO21702:2019. That is, a virus-containing liquid related to influenza A virus was inoculated into each of Examples 1 to 6 and Comparative Examples 1 to 4 and an unprocessed product, with the virus infectivity value being known. The virus infectivity value is the number of infective viruses. The unprocessed product has a structure corresponding to only the substrate 2 in Examples 1 to 6 and Comparative Examples 1 to 4, and serves as a reference. More specifically, regarding the inoculation, the virus-containing liquid was dropped onto the surface of each dielectric multilayer film 4 or the surface of the unprocessed product, and the virus-containing liquid was covered with a separate film to ensure the adhesion of the virus-containing liquid to the dielectric multilayer film 4 or the unprocessed product. Then, Examples 1 to 6, Comparative Examples 1 to 4, and the unprocessed product were left for 24 hours, and the virus infectivity 24 hours after inoculation was measured after removing the film. The virus infectivity after 24 hours in Examples 1 to 6 and Comparative Examples 1 to 4 was designated as virus infectivity A. The virus infectivity after 24 hours in the unprocessed product was designated as virus infectivity B. In the antiviral test, potentially infectious influenza viruses are handled under strict control, and the number of viruses is counted after a certain period of time. Therefore, it takes time and costs to perform the antiviral test. Even if the antiviral test is outsourced to a specialist, the recent interest in viruses has led to an increase in other orders, so it still takes time and costs to perform the antiviral test.

[0052] For the virus infectivity titers A and B, the following two types of values, that is, the antiviral activity value R and the infectious virus reduction rate D, were calculated, respectively, to evaluate the antiviral performance of Examples 1 to 6 and Comparative Examples 1 to 4. Each antiviral activity value R and infectious virus reduction rate D are shown on the right side of Table 3 above.

[0053] As a first value, an antiviral activity value R was calculated. The antiviral activity value R is calculated by the following formula (2). The larger the value of the antiviral activity value R, the higher the antiviral performance. R=log 10 (B / A) ···(2) Here, A is the viral infectivity after 24 hours in any one of Examples 1 to 6 and Comparative Examples 1 to 4, B is the viral infectivity after 24 hours in an unprocessed product, and R is the antiviral activity value.

[0054] The antiviral activity values ​​R of Examples 1 and 2 were 4.4. The antiviral activity value R of Example 3 was 0.7. The antiviral activity value R of Example 4 was 0.8. The antiviral activity value R of Example 5 was 1.5. The antiviral activity value R of Example 6 was 2.0. The antiviral activity value R of Comparative Example 1 was 2.3. The antiviral activity value R of Comparative Example 2 was 0.2. The antiviral activity value R of Comparative Example 3 was 0.0. The antiviral activity value R of Comparative Example 4 was 1.2.

[0055] As a second value, the infectious virus reduction rate D was calculated. The infectious virus reduction rate D is calculated by the following formula (3). The larger the infectious virus reduction rate D, the higher the antiviral performance. The infectious virus reduction rate D is expressed in units of %. Note that the infectious virus reduction rate D is not defined in ISO21702:2019. D = {1-(A / B)} × 100 (3) Here, A is the virus infectivity after 24 hours in any one of Examples 1 to 6 and Comparative Examples 1 to 4, B is the virus infectivity after 24 hours in an unprocessed product, and D is the infectious virus reduction rate.

[0056] The infectious virus reduction rate D of Examples 1 and 2 was 99.99% or more. The infectious virus reduction rate D of Example 3 was 80.04%. The infectious virus reduction rate D of Example 4 was 84.15%. The infectious virus reduction rate D of Example 5 was 96.84%. The infectious virus reduction rate D of Example 6 was 99.00%. The infectious virus reduction rate D of Comparative Example 1 was 99.50%. The infectious virus reduction rate D of Comparative Example 2 was 36.90%. The infectious virus reduction rate D of Comparative Example 3 was 0.00%. The infectious virus reduction rate D of Comparative Example 4 was 90.00%.

[0057] Examples 1-2 and Comparative Example 1 are discussed below. In Comparative Example 1, which has a layer with a physical thickness of 50 nm containing 50 wt% silver ion-supported zeolite, which is not covered with an anti-fouling layer 12 and is not irradiated with ultraviolet rays, the antiviral activity value R is 2.3 and the infectious virus reduction rate D is 99.50%. In contrast, in Example 1 having an antiviral layer 10 that contains 50 wt% silver ion-supported zeolite, has a physical thickness of 50 nm, is not covered by an antifouling layer 12, and is irradiated with ultraviolet light for 5 minutes, the antiviral activity value R is 4.4 and the infectious virus reduction rate D is 99.99% or more.In Example 2 having an antiviral layer 10 that contains 50 wt% silver ion-supported zeolite, has a physical thickness of 50 nm, is not covered by an antifouling layer 12, and is irradiated with ultraviolet light for 10 minutes, the antiviral activity value R is 4.4 and the infectious virus reduction rate D is 99.99% or more. In other words, by irradiation with ultraviolet rays, the antiviral performance of the dielectric multilayer film 4, which includes a layer with a physical thickness of 50 nm containing 50 wt% silver ion-supported zeolite and which is not covered with the antifouling layer 12, improves from 2.3 to 4.4 in terms of antiviral activity value R, and from 99.50% to more than 99.99% in terms of infectious virus reduction rate D.

[0058] Examples 3-4 and Comparative Example 2 are discussed below. In Comparative Example 2, which has a layer with a physical thickness of 50 nm containing 50 wt% silver ion-supported zeolite, which is covered with an anti-fouling layer 12 and is not irradiated with ultraviolet rays, the antiviral activity value R is 0.2 and the infectious virus reduction rate D is 36.90%. In contrast, in Example 3 having an antiviral layer 10 that is a layer with a physical thickness of 50 nm containing 50 wt% silver ion-supported zeolite, that is covered with an antifouling layer 12, and that is irradiated with ultraviolet light for 5 minutes, the antiviral activity value R is 0.7 and the infectious virus reduction rate D is 80.04%.In Example 4 having an antiviral layer 10 that is a layer with a physical thickness of 50 nm containing 50 wt% silver ion-supported zeolite, that is covered with an antifouling layer 12, and that is irradiated with ultraviolet light for 10 minutes, the antiviral activity value R is 0.8 and the infectious virus reduction rate D is 84.15%. In other words, by irradiation with ultraviolet light for 5 and 10 minutes, the antiviral performance of the dielectric multilayer film 4 including a layer with a physical thickness of 50 nm containing 50 wt% silver ion-supported zeolite and covered with an antifouling layer 12 improves in terms of antiviral activity value R from 0.2 to 0.7 and 0.8, respectively, and in terms of infectious virus reduction rate D from 36.90% to 80.05% and 84.15%, respectively.

[0059] Example 5 and Comparative Example 3 are discussed below. In Comparative Example 3, which has a layer with a physical thickness of 30 nm containing 40 wt% silver ion-supported zeolite, which is not covered with an anti-fouling layer 12 and is not irradiated with ultraviolet rays, the antiviral activity value R is 0.0 and the infectious virus reduction rate D is 0.00%. In contrast, in Example 5 having an antiviral layer 10 that is a layer with a physical thickness of 30 nm containing 40 wt % silver ion-supported zeolite, is not covered with an antifouling layer 12, and is irradiated with ultraviolet light for 5 minutes, the antiviral activity value R is 1.5 and the infectious virus reduction rate D is 96.84%. In other words, by irradiation with ultraviolet rays for 5 minutes, the antiviral performance of the dielectric multilayer film 4, which includes a layer containing 40 wt% silver ion-supported zeolite and having a physical thickness of 30 nm and which is not covered with the antifouling layer 12, improves from 0.0 to 1.5 in terms of antiviral activity value R and from 0.00% to 96.84% in terms of infectious virus reduction rate D.

[0060] Example 6 and Comparative Example 4 are discussed below. In Comparative Example 4, which has a layer with a physical thickness of 100 nm containing 40 wt% silver ion-supported zeolite, which is not covered with an anti-fouling layer 12 and is not irradiated with ultraviolet rays, the antiviral activity value R is 1.0 and the infectious virus reduction rate D is 90.00%. In contrast, in Example 6 having an antiviral layer 10 that contains 40 wt % silver ion-supported zeolite, has a physical thickness of 100 nm, is not covered with an antifouling layer 12, and is irradiated with ultraviolet light for 10 minutes, the antiviral activity value R is 2.0 and the infectious virus reduction rate D is 99.00%. In other words, by irradiation with ultraviolet rays for 10 minutes, the antiviral performance of the dielectric multilayer film 4, which includes a layer containing 40 wt% silver ion-supported zeolite and having a physical thickness of 100 nm, and which is not covered with the antifouling layer 12, improves from 1.0 to 2.0 in terms of antiviral activity value R, and from 90.00% to 99.00% in terms of infectious virus reduction rate D.

[0061] The configurations and effects of Examples 1 to 6 will be mainly summarized below. Examples 1 to 6 include a dielectric multilayer film 4 having anti-reflection properties. The dielectric multilayer film 4 of Examples 1 to 6 includes three (Examples 1 to 5) or two (Example 6) low refractive index dielectric layers 6, two high refractive index dielectric layers 8, and an antiviral layer 10. The antiviral layer 10 is a dielectric layer including metal ion-supported zeolite, and is disposed closer to the atmosphere than all of the low refractive index dielectric layers 6 and all of the high refractive index dielectric layers 8, and is irradiated with high energy rays while including metal ion-supported zeolite. The manufacturing methods of Examples 1 to 6 include a step of forming three (Examples 1 to 5) or two (Example 6) low refractive index dielectric layers 6 and two high refractive index dielectric layers 8 alternately, and then forming a manufacturing intermediate antiviral layer, which is a dielectric layer containing metal ion-supported zeolite, to form a manufacturing intermediate film having antireflective properties, and a step of irradiating the manufacturing intermediate antiviral layer with high-energy rays to convert the manufacturing intermediate antiviral layer into antiviral layer 10. Therefore, the antiviral properties of the dielectric multilayer film 4 having an antireflection function are improved by a method other than increasing the amount of metal ion-supported zeolite.

[0062] In addition, in Examples 1 to 6 and the manufacturing methods thereof, the high energy rays are ultraviolet rays, so that the antiviral properties of the dielectric multilayer film 4 can be more easily achieved. Furthermore, in Examples 1 to 6 and the manufacturing methods thereof, the time of irradiation with high energy rays is 5 minutes within the range of 1 minute to 20 minutes in Examples 1, 3, and 5, and 10 minutes within the range of 1 minute to 20 minutes in Examples 2, 4, and 6. Therefore, sufficient antiviral properties can be obtained more efficiently. Furthermore, the physical film thickness of the antiviral layer 10 is 50 nm in the range of 30 nm to 100 nm in Examples 1 to 4, 30 nm in the range of 30 nm to 100 nm in Example 5, and 100 nm in the range of 30 nm to 100 nm in Example 6. Therefore, sufficient antiviral properties are obtained without impairing the antireflection function of the dielectric multilayer film 4. In addition, the mass ratio of the metal ion-supported zeolite in the antiviral layer 10 is 50 wt% in the range of 30 wt% to 60 wt% in Examples 1 to 4, and 40 wt% in the range of 30 wt% to 60 wt% in Examples 5 and 6. Therefore, the influence of a decrease in the transmittance of the antiviral layer 10 is suppressed, and sufficient antiviral properties are obtained while the antireflection function of the dielectric multilayer film 4 is not easily hindered. In addition, in Examples 1 to 6 and the manufacturing method thereof, the metal ion-supported zeolite is a silver ion-supported zeolite, and thus the antiviral property and durability of the dielectric multilayer film 4 having an antireflection function are improved by using the silver ion-supported zeolite having better antiviral performance per unit mass and better durability against water.

[0063] Furthermore, in Examples 1 to 6 and the manufacturing methods thereof, the antiviral layer 10 contains SiO2. Therefore, the metal particles 14 are more stable in the antiviral layer 10. Moreover, the antiviral layer 10 can be optically treated as a layer similar to a SiO2 layer, and the dielectric multilayer film 4 can be more easily designed. Furthermore, in Examples 1 to 6 and the manufacturing methods thereof, the antiviral layer 10 is formed of a sintered body obtained by sintering together metal ion-supported zeolite and SiO2, which makes it easier to form the antiviral layer 10.

[0064] Additionally, in Examples 3 and 4 and their manufacturing methods, the dielectric multilayer film 4 includes an antifouling layer 12 exhibiting at least one of water repellency and oil repellency. The antifouling layer 12 is formed after the step of irradiating the intermediate antiviral layer with ultraviolet light during manufacturing, and is disposed closer to the atmosphere than the antiviral layer 10. Thus, the dielectric multilayer film 4 provides antifouling performance without blocking the antiviral property of the antiviral layer 10. In addition, the antifouling layer 12 is a fluorine-containing organosilicon compound, so that the antifouling layer 12 is more easily formed.

[0065] Furthermore, in Examples 1 to 6 and the manufacturing methods thereof, the optical product 1 includes a dielectric multilayer film 4 and a substrate 2. The dielectric multilayer film 4 is formed directly or indirectly on the film placement surface F of the substrate 2. Thus, the optical product 1 is provided with an antireflection film having excellent antiviral performance. In addition, in Examples 1 to 6 and the manufacturing methods thereof, the base material 2 is made of plastic, which provides an optical product 1 with greater durability. Furthermore, in Examples 1 to 6 and the manufacturing methods thereof, the dielectric multilayer film 4 is formed via a hard coat film (intervening film 3), thereby providing an optical product 1 with even greater strength. [Explanation of symbols]

[0066] 1 optical product, 2 substrate, 3 intermediate film (hard coat film), 4 dielectric multilayer film (antiviral antireflection film), 6 low refractive index dielectric layer, 8 high refractive index dielectric layer, 10 antiviral layer, 12 antifouling layer, F film placement surface, S1 (formation of intermediate film), S2 (irradiation of high energy rays), S4 (formation of antifouling layer 12).

Claims

1. Anti-reflective dielectric multilayer film Equipped with The dielectric multilayer film includes one or more low refractive index dielectric layers, one or more high refractive index dielectric layers, and an antiviral layer; The antiviral layer comprises: a dielectric layer including a metal ion-supported zeolite; The dielectric layer is disposed on the air side of all the low refractive index dielectric layers and all the high refractive index dielectric layers, The metal ion-supported zeolite is irradiated with high energy rays. An antiviral antireflective film characterized by:

2. The high energy radiation is ultraviolet radiation. The antiviral antireflective film according to claim 1 .

3. The duration of the irradiation of the high energy beam is from 1 minute to 20 minutes. The antiviral antireflective film according to claim 1 .

4. The physical thickness of the antiviral layer is 30 nm or more and 100 nm or less. The antiviral antireflective film according to claim 1 .

5. The mass ratio of the metal ion-supported zeolite in the antiviral layer is 30 wt % or more and 60 wt % or less. The antiviral antireflective film according to claim 1 .

6. The metal ion-supported zeolite is a silver ion-supported zeolite. The antiviral antireflective film according to claim 1 .

7. The antiviral layer is made of SiO 2 Contains The antiviral antireflective film according to claim 1 .

8. The antiviral layer is made of the metal ion-supported zeolite and SiO 2 It is made of a sintered body made by sintering The antiviral antireflective film according to claim 7 .

9. the dielectric multilayer film has an antifouling layer exhibiting at least one of water repellency and oil repellency; The antifouling layer is disposed closer to the atmosphere than the antiviral layer. The antiviral antireflective film according to claim 1 .

10. The antifouling layer is a fluorine-containing organosilicon compound. The antiviral antireflective film according to claim 9 .

11. A dielectric multilayer film according to any one of claims 1 to 10, A substrate; An optical product comprising: The dielectric multilayer film is formed directly or indirectly on the film-arrangement surface of the substrate. An optical product characterized by:

12. The substrate is made of plastic.

12. The optical product according to claim 11.

13. The dielectric multilayer film is formed via a hard coat film.

12. The optical product according to claim 11.

14. A step of forming one or more low refractive index dielectric layers and one or more high refractive index dielectric layers alternately, and then forming a manufacturing intermediate antiviral layer which is a dielectric layer containing metal ion-supported zeolite, thereby forming a manufacturing intermediate film having antireflective properties; a step of converting the intermediate antiviral layer into an antiviral layer by irradiating the intermediate antiviral layer with a high-energy ray; Equipped with A method for producing an antiviral antireflective film, comprising the steps of:

15. The high energy radiation is ultraviolet radiation. The method for producing an antiviral antireflection coating according to claim 14.

16. The time for irradiating the high energy beam is from 1 minute to 20 minutes. The method for producing an antiviral antireflection coating according to claim 14.

17. The physical thickness of the antiviral layer is 30 nm or more and 100 nm or less. The method for producing an antiviral antireflection coating according to claim 14.

18. The mass ratio of the metal ion-supported zeolite in the intermediate antiviral layer is 30 wt % or more and 60 wt % or less. The method for producing an antiviral antireflection coating according to claim 14.

19. The metal ion-supported zeolite is a silver ion-supported zeolite. The method for producing an antiviral antireflection coating according to claim 14.

20. The antiviral layer is made of SiO 2 Contains The method for producing an antiviral antireflection coating according to claim 14.

21. The intermediate antiviral layer is made of the metal ion-supported zeolite and SiO 2 It is made of a sintered body made by sintering The method for producing an antiviral antireflective coating according to claim 20.

22. The method further includes a step of forming an antifouling layer exhibiting at least one of water repellency and oil repellency after the step of forming the manufactured intermediate film or after the step of irradiating the high energy ray. The method for producing an antiviral antireflection coating according to claim 14.

23. The antifouling layer is a fluorine-containing organosilicon compound. The method for producing an antiviral antireflective coating according to claim 22.

24. A method for producing an optical product, comprising the method for producing the antiviral antireflection coating according to any one of claims 14 to 23, The intermediate film is directly or indirectly formed on the film placement surface of the substrate. A method for producing an optical product comprising the steps of:

25. The substrate is made of plastic.

25. A method for producing an optical product according to claim 24.

26. The intermediate film is formed via a hard coat film.

25. A method for producing an optical product according to claim 24.

Citation Information

Patent Citations

  • Antiviral transparent laminate

    JP2022109847A